FAKTOR-FAKTOR INTERNAL YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Jessica Vianto, Sugi Suhartono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
This study aims to analyze the internal factors that affect the premature sign-off. These internal factors are the locus of control, self-esteem in relation to ambition, turnover intentions and the auditor's experience of premature sign-off of audit procedure.This research was conducted by distributing questionnaires to 23 Non-Big-Four Public Accountant Firm in Jakarta and getting 108 auditors as respondents. The results of this study indicate that the locus of control has a significant value of 0.000. The significant value of the self-esteem in relation to ambition of0.099. While the significant result of turnover intention is 0.110. And the auditor's experience is 0.001. It was concluded that the proven locus of control had a positive effect on premature sign-off of the audit procedure, while there was insufficient evidence that self-esteem associated with ambition and stopping desire had a positive effect on the premature sign-off of audit procedures. Nor is it sufficient evidence that the auditor's experience negatively affects premature sign-off of audit procedures.Keywords : Premature sign off, Locus of control, Self esteem, Turnover intentions